Explorando as capacidades do Método Wavelet para modelagem de propagação de ondas de rádio: um enfoque em eficiência e precisão na predição de cobertura radioelétrica - Alexandre Alves da Rocha (2024)
In this work, a comprehensive analysis of the Split-Step Wavelet Method applied to the solution of the Parabolic Equations (SSW-PE) in modeling radio wave propagation is presented. The SSW-PE introduces significant innovations, such as the application of narrow and wide beam angle approaches, referred to as NAPE and WAPE, respectively. Additionally, variations in refractivity, modifications in terrain modeling for better representation, and considerations of mixed surface boundary conditions are incorporated. The detailing and imposition of sampling criteria to prevent numerical instabilities and the consequent amplification of errors and numerical oscillations are also highlighted. The objective of this thesis is to explore these innovative aspects and provide a complete guide for the effective replication of the algorithm, promoting the advancement of propagation studies using Wavelets. The effectiveness and applicability of this approach are validated through comparative studies with well-established solutions, including the version of the Split-Step Fourier Method with Discrete Mixed Transform for solving the Parabolic Equations (DMFT-SSPE). Additionally, comparisons with measurement campaigns of real propagation cases are conducted. Statistical analysis confirms the innovative potential of the SSW-PE algorithm, which also offers computational efficiency for fast and consistent simulations. Thus, this thesis contributes a comprehensive and innovative analysis, providing tangible resources for the research community interested in expanding this methodology. In summary, this study successfully introduces an innovative approach to solve parabolic equations in radio coverage predictions, focusing on the SSW-PE method, a remarkable advancement in computational efficiency. The promising results confirm its revolutionary potential in electromagnetic propagation modeling, especially in realistic environments.